EFFICACY OF EGG YOLK FROM THREE AVIAN SPECIES ON SEMEN FREEZABILITY OF THARPARKAR BULL - SINGH, MAHAK; RAMTEKE, SNEHAL S; GHOSH, S K; PRASAD, J K; RAJORIYA, J S (The Indian Journal of Animal Reproduction, 2023)
Egg yolk is one of the most widely used cryoprotective components for sperm preservation and a wide range of factors affect its action on sperm motility, viability and fertilizing ability. The aim of this experiment was to determine the effect of different species egg yolk, namely the domestic chicken (Gallus domesticus), duck (Anas platyrhynchos) and Japanase quail (Coturmixjaponica) on sperm quality following cryopreservation ofTharparkar bull semen. A total of 30 ejaculates from three bulls (1 O from each bull) were used in the experiment. Each ejaculate was divided into three equal parts and diluted with three different extenders with 20 per cent egg yolk from domestic chicken (Gallus domesticus) (CEY), domestic duck (Anas platyrhynches) (DEY) and Japanase quail (Coturnixjaponica) (QEY). The semen straws were equilibrated at4°C for4 hrs and freezing was done using biological cell freezer (-140°C) and stored in liquid nitrogen (-196 °C). After thawing (37°C for 30 s), sperm motility, viability, acrosomal integrity and membrane integrity (HOST) were evaluated. The post extension sperm motility did not differ among three extenders. Result of present experiment showed that QEY based tris extender had better post-thaw motility, viability, acrosomal integrity and membrane integrity (HOST) (p<0.01) in comparison to CEY and DEY based tris extender.